Pulsed electric field processing of white grapes (cv. Garganega): Effects on wine composition and volatile compounds. (30th October 2018) - Comuzzo, Piergiorgio; Marconi, Marco; Zanella, Gianmaria; Querzè, Marco
Highlights: PEF pre-treatment of white grapes did not change basic composition of musts and wines. PEF pre-treatment of grapes did not modify the behavior of alcoholic fermentation. PEF increased the extraction of varietal aroma precursors from grapes. At 22 kJ kg −1 specific energy (SE), PEF gave a limited evolution of wine color. At 22 kJ kg −1 SE, PEF apparently increased the stability of wine towards oxidations. Abstract: Pulsed electric field (PEF) processing of white grapes (cv. Garganega) after crushing was studied on pilot-plant scale, to investigate the effects of the treatment on must and wine composition, wine color and predisposition to browning, wine aroma compounds and extraction of aroma precursors from grapes. PEF pre-treatment of grapes did not change the must or wine basic composition, nor was it able to modify the evolution of alcoholic fermentation. By contrast, PEF produced an increase in total dry extract, wine color and total phenolics. Treatment corresponding to a total specific energy of 22 kJ kg −1 allowed more intense extraction of varietal aroma precursors without provoking excessive color evolution and extraction of phenolic compounds, apparently increasing the stability of wine towards oxidation. Due to the few papers available on this subject, PEF applications on white grapes should be optimized in further experiments.